Prilaku Simbolis Jama’ah Tabligh: (Studi Kasus Dinamika Kehidupan Beragama Jama’ah Tabligh di Kota Banda Aceh) (An-Nasyr, 2024)
Symbolic behavior in the context of the Tablighi Jama'ah includes various practices, including the use of typical clothing, the practice of shaking hands, the practice of eating together, the way of walking, and the emphasis on preaching and religious activities. Some people see this symbolic behavior as a form of expression of strong faith, while others see it as self-isolation.This research uses a descriptive method with a phenomenological approach. Primary data sources and secondary data, primary data sources in this research are works and books which are the main guidelines for the Tablighi Jama'ah. Meanwhile, secondary data from this research are the works of experts in their respective fields. The research results show that the religious symbols and behavior practiced by the Tablighi Jama'ah have given rise to various interpretations among Muslims. These differences in interpretation are caused by differences in viewpoints in understanding one group versus another, which can lead to divisions. Even though Islam is a religion of rahmatan lil 'alamin which protects all its adherents.